Activity Ratio to Measure Performance at PT. Jesry Karya Engenering Makassar City - Lukman, Siti Diva Syarifah (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2024)
This article analyzes the activity ratio in measuring the performance of PT. Jesry Karya Engenering Makassar. The purpose of this article is to understand the extent to which the company is able to manage and utilize its assets efficiently to support the company’s operational activities. This article uses a quantitative descriptive approach with data collection methods through documentation, specifically utilizing the company’s financial reports (balance sheets and income statements for the 2019-2021 period). The data analysis technique used is by calculating the ratio then the calculation result will be interpreted to conclude the ratio result with the company performance. From the findings, it is found that the performance of PT. Jesry Karya Engenering Makassar as measured by the ratio of accounts receivable turnover, working capital turnover, and asset turnover is still relatively low. However, if measured from the inventory turnover ratio, the performance of PT. Jesry Karya Engenering Makassar is quite high.